6281335119014 PENGARUH KOREKSI POSTUR TERHADAP PENURUNAN NYERI PINGGANG BAWAH PADA MAHASISWA SEBAGAI DAMPAK KEGIATAN PEMBELAJARAN SECARA VIRTUAL - Nia Kurniawati; Ahmad Syakib; Jerry Maratis (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Sitting for long hours during virtual learning will cause a musculoskeletal disorder in the lower spine which is commonly known as low back pain.Interventions that can be done to treat low back pain are through posture correction exercises, which are exercises to correct unstable muscles, bad posture and muscle pain caused by changes in posture by teaching someone good posture.Objective: To determine the effect of posture correction on reducing low back pain in college students. Research design: pre-experimental using a